Diffusion Tensor Imaging of the Olfactory System in Older Adults With and Without Hyposmia - Felix, Cynthia; Chahine, Lana M.; Hengenius, James; Chen, Honglei; Rosso, Andrea L.; Zhu, Xiaonan; Cao, Zichun; Rosano, Caterina (Frontiers in Aging Neuroscience, 2021)
Objectives: To compare gray matter microstructural characteristics among older adults with and without hyposmia. Methods: Data from the Brief Smell Identification Test (BSIT) were obtained in 1998-99 for 264 dementia-free adults from the Health, Aging, and Body Composition study (age at BSIT: 74.9±2.7; 62% White; 43% male) who received 3T diffusion tensor imaging (DTI) MRI in 2006-08 [Interval of time: mean (SD): 8.01 years ( 0.50)], 3MS assessments randomly throughout the study, and cognitive adjudication in 2011-12. Hyposmia was defined as BSIT≤8. Gray matter integrity was quantified by mean diffusivity (MD) in orbitofrontal cortex (OFC, including olfactory cortex, gyrus rectus, the orbital parts of the superior, middle, and inferior frontal gyri, medial orbital part of the superior frontal gyrus), piriform and entorhinal cortices, amygdala, hippocampus, and thalamus. All models were adjusted for total brain atrophy, demographics, 3MS at the time of BSIT, and ApoEƐ4 genotype. Results: Hyposmia in 1998-99 (n=57, 21.59%) was significantly associated with greater MD (lower microstructural integrity) in the OFC in 2006-08, specifically in the left superior frontal gyrus, medial orbital part, and in the left and right gyri recti [unadjusted beta (p value): 0.514 (0.03); 0.624 (0.01); 0.695 (0.01) respectively]. Conclusions: Older adults with less microstructural integrity in the OFC are more likely to have had previous hyposmia. Future studies should address whether hyposmia can serve as an early biomarker of covert brain structural abnormalities for older adults with a range of cognitive functions, even for adults who remain cognitively normal late in life.